Odpowiedzi

2010-02-18T20:16:33+01:00
-4(-2x+6y+5z)-8(9x+8y-7z)+5(3x-6y+9z)= 8x-24y-20z-72x-64y+56z+15x-30y+45z=-49x+10y+81z
3(a+2b-3c)+7(2a-4b+5c) -5(-3a-4b-5c)= 3a+6b-9c+14a-28b+35c+15a+20b+25c=32a+54b+51c
2/3 (3a +6b-12c)+ 3/5 (10a-15b+20c) =2a+4b-8c+3a-9b+12c=5a-5b+4c
Najlepsza Odpowiedź!
2010-02-18T20:23:42+01:00
-4(-2x+6y+5z)-8(9x+8y-7z)+5(3x-6y+9z)=
8x - 24y - 20z - 72x - 64y + 56z + 15x - 30y + 45z =
- 49x - 188y + 81z


3(a+2b-3c)+7(2a-4b+5c) -5(-3a-4b-5c)=
3a +6b - 9c + 14a - 28b + 35c +15a + 20b + 25c =
32a - 2b + 51c


2/3 (3a +6b-12c)+ 3/5 (10a-15b+20c) =
2a + 4b - 8c + 6a - 9b + 12c =
8a - 5b + 4c